Knowledge and Factors Associated with Overweight and Obesity Prevention among Women Attending Kibagabaga Hospital, Rwanda - Niyitegeka Alexis; Habtu Micheal; Vasanthakaalam Hilda; Rutayisire Erigene (Journal of Public Health International, 2021)
Women in Rwanda are still suffering from overweight and obesity and health-related complications. However, little is known about overweight/obesity prevention knowledge and factors associated with overweight/obesity prevention among women. The aim of this study was to determine knowledge and factors associated with overweight and obesity prevention among women attending Kibagabaga Hospital in Rwanda. A quantitative descriptive cross-sectional design was conducted among women aged 20-45 years that was selected randomly. A structured questionnaire was used to collect data from 384 women seeking health care at the hospital during the study period. SPSS version 21 was used for data analysis; descriptive statistics was used to assess women’s knowledge related to overweight/obesity. Logistic regression was used to determine the factors associated with overweight/obesity prevention, the level of significance was set at 5%. Approval to conduct the study was obtained from the University and Hospital. The majority 35.4% of study participants were aged between 30-34 years. Women who live in urban area dominate the study (76.3%), the majority of study participants were married (60.9%). The study revealed that the 22% and 62% of women had higher level and moderate knowledge respectively. In terms of overweight/obesity prevention practices, we found that 67% mothers had adequate practices towards overweight and obesity prevention. The age of 35-39, and unemployment were found to be significantly associated with overweight/obesity prevention practices. Cost-effective health education focusing on women, physical activity and social support to reduce the socio-cultural constraints that promote overweight/obesity are necessary to combat this epidemic.
Keywords: Overweight